Basketball - Rosenthal, Bert. (New York : Childrens Press, 1995)
Explains the fundamental aspects of basketball, including equipment, scoring, game rules, players and officials, and contrasts professional basketball with the high school and college sport.
Includes index.
3.8
K-3
Keywords: Basketball -- Juvenile literature; Basketball; Basketball